Asymmetric accretion and thermal 'mountains' in magnetized neutron star crusts. Issue 3 (14th February 2020) - Singh, N; Haskell, B; Mukherjee, D; Bulik, T
ABSTRACT: Accreting neutron stars (NSs) are one of the main targets for continuous gravitational wave searches, as asymmetric accretion may lead to quadrupolar deformations, or 'mountains', on the crust of the star, which source gravitational wave (GW) emission at twice the rotation frequency. The GW torque may also impact on the spin evolution of the star, possibly dictating the currently observed spin periods of NSs in low-mass X-ray binaries and leading to the increased spin-down rate observed during accretion in PSR J1023+0038. Previous studies have shown that deformed reaction layers in the crust of the NS lead to thermal and compositional gradients that can lead to GW emission. However, there are no realistic constraints on the level of asymmetry that is expected. In this paper, we consider a natural source of asymmetry, namely the magnetic field, and calculate the density and pressure perturbations that are expected in the crust of accreting NSs. In general, we find that only the outermost reaction layers of the NS are strongly perturbed. The mass quadrupole that we estimate is generally small and cannot explain the increase of spin-down rate of PSR J1023+0038. However, if strong shallow heating sources are present at low densities in the crust, as cooling observations suggest, these layers will be strongly perturbed and the resulting quadrupole could explain the observed spin-down of PSR J1023+0038, and lead to observable GW signals from systems with higher accretion rates.